APPLICATION OF MINDFULNESS-BASED COGNITIVE THERAPY (MBCT) TO IMPROVE SELF-REGULATION IN STUDENTS EXPERIENCING SCHOOL DISENGAGEMENT: A LITERATURE REVIEW - Klaudia Sartika Dabur; Eka Wahyuni; Karsih Karsih (LP2M IAI Al-Khairat Pamekasan, 2026)
School disengagement is a common problem, which can negatively impact students' motivation, academic performance, and emotional well-being. Mindfulness-based cognitive therapy has shown promise for addressing these challenges by improving self-regulation and reducing school disengagement. This systematic review analyzed recent literature (2019-2025) from databases such as Google Scholar, Scopus, and PubMed, by selecting relevant studies through PRISMA. Findings showed that mindfulness-based cognitive therapy significantly improved emotion regulation, awareness, and coping strategies, while reducing anxiety and stress among students, and promoting increased engagement in learning. OveralSchool disengagement is a common problem, which can negatively impact students' motivation, academic performance, and emotional well-being. Mindfulness-based cognitive therapy has shown promise for addressing these challenges by improving self-regulation and reducing school disengagement. This systematic review analyzed recent literature (2019-2025) from databases such as Google Scholar, Scopus, and PubMed, by selecting relevant studies through PRISMA. Findings showed that mindfulness-based cognitive therapy significantly improved emotion regulation, awareness, and coping strategies, while reducing anxiety and stress among students, and promoting increased engagement in learning. Overall, mindfulness-based cognitive therapy is an effective approach to improve self-regulation and reduce student disengagement in school. The potential integration of mindfulness-based cognitive therapy in psychological prevention and intervention programs in the school setting is important to support the improvement of students' well-being and academic success, particularly through strengthening self-regulation skills and reducing factors that lead to school disengagement.l, mindfulness-based cognitive therapy is an effective approach to improve self-regulation and reduce student disengagement in school. The potential integration of mindfulness-based cognitive therapy in psychological prevention and intervention programs in the school setting is important to support the improvement of students' well-being and academic success, particularly through strengthening self-regulation skills and reducing factors that lead to school disengagement.